1996
DOI: 10.1111/j.1432-1033.1996.0537r.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Inhibits the Lowering Effect of Glucose on the Level of Phosphoenol pyruvate Carboxykinase mRNA in Isolated Rat Hepatocytes

Abstract: The expression of phosphoenolpyruvate carboxykinase (P-pyruvate CK) was shown to be decreased by hypoosmolarity and increased by glutamine in perfused liver from fed rats [Newsome, W. P., Warskulat, U., Noe, B., Wettstein, M., Stoll, B., Gerok, W. & Haussinger, D. (1994) Biochern. J . 304, 555-5601, This work was undertaken to specify the mechanisms of glutamine action, using isolated hepatocytes from rats that had been starved for 24 h. At low concentrations (up to 5 mM), glutamine elicited a decrease in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…In this work, the increase in the PEPCK mRNA level after 24 h of the hyperosmotic stress led to the increase of the gluconeogenic and PEPCK activities as consequence of the metabolism of amino acids in muscle. In mammals it was suggested that glutamine may regulate the PEPCK gene expression through two di¡erent mechanisms: the glutamineinduced cell swelling, decreasing the mRNA level, and another unidenti¢ed mechanism, depending on its metabolism, that increases the mRNA level [7,24].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, the increase in the PEPCK mRNA level after 24 h of the hyperosmotic stress led to the increase of the gluconeogenic and PEPCK activities as consequence of the metabolism of amino acids in muscle. In mammals it was suggested that glutamine may regulate the PEPCK gene expression through two di¡erent mechanisms: the glutamineinduced cell swelling, decreasing the mRNA level, and another unidenti¢ed mechanism, depending on its metabolism, that increases the mRNA level [7,24].…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine at low concentrations (up to 5 mM) elicited a decrease of PEPCK mRNA, through cell swelling but at higher concentrations, an increase in the mRNA level was observed. 31 This latter effect seems to result from glutamine metabolism by an unknown mechanism. Lavoinne et al reported that 10 mM glutamine increases the level of PEPCK mRNA in perfused rat liver.…”
Section: Hepatocytesmentioning
confidence: 98%
“…Glucose, in contrast to other factors, has opposing effects on PEPCK and G6PC1 gene expression, as it downregulates PEPCK (15) and upregulates G6Pase (40). Glutamine has been shown to counteract the effect of glucose on PEPCK gene expression (35), but no study has examined the effect of a physiological increase of amino acid availability on the regulation of PEPCK and G6PC1 gene expression in gluconeogenic organs. There is, however, some evidence that glucose alone is not a good precursor for hepatic glycogen synthesis in vitro in perfused rat liver (26) or in isolated hepatocytes (21,31) and that the addition of modest amounts of gluconeogenic substrates in the culture medium (lactate or amino acids) results in markedly enhanced glycogenesis (7,47).…”
mentioning
confidence: 99%